Major court and tribunal decisions in Australia in 2018. (June 2019) - Landau, Ingrid; Allen, Dominique
The year 2018 saw significant tribunal and court decisions concerning the definition of 'casual' for the purposes of the National Employment Standards, the obligations of labour hire employers, and the employment status of food delivery drivers in the gig economy. This review also covers a number of significant changes to awards made by the Fair Work Commission as part of its 4-yearly award review; a Full Federal Court decision about the extent to which a small group of employees genuinely agreed to approve an enterprise agreement. An unusual tribunal decision about an employee who was assumed to have a disability is noted. Finally, the review considers several significant judicial decisions on accessorial liability and penalites under the Fair Work Act.